2014
DOI: 10.3389/fncel.2014.00183
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 type 1 receptor signaling up-regulates KCNN4 expression, and increases the KCa3.1 current and its contribution to migration of alternative-activated microglia

Abstract: The Ca2+-activated K+ channel, KCa3.1 (KCNN4/IK1/SK4), contributes to “classical,” pro-inflammatory activation of microglia, and KCa3.1 blockers have improved the outcome in several rodent models of CNS damage. For instance, blocking KCa3.1 with TRAM-34 rescued retinal ganglion neurons after optic nerve damage in vivo and, reduced p38 MAP kinase activation, production of reactive oxygen and nitrogen species, and neurotoxicity by microglia in vitro. In pursuing the therapeutic potential of KCa3.1 blockers, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 78 publications
(143 reference statements)
9
89
2
1
Order By: Relevance
“…IL13 mediates its effects by interacting with a complex receptor system comprising of IL4Rα and two IL13 binding proteins, IL13Rα1 and IL13Rα2. However, unlike IL4, IL13 does not appear to be important in the initial differentiation of cluster of differentiation 4 (CD4) T-naive T-cells into TH2 cells, because there are no functional IL13 receptors on human Tcells (33)(34)(35). Rather, IL13 is related to fibrosis of tissue in various chronic types of inflammation because IL13Rs are expressed on endothelial cells, fibroblasts, and smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL13 mediates its effects by interacting with a complex receptor system comprising of IL4Rα and two IL13 binding proteins, IL13Rα1 and IL13Rα2. However, unlike IL4, IL13 does not appear to be important in the initial differentiation of cluster of differentiation 4 (CD4) T-naive T-cells into TH2 cells, because there are no functional IL13 receptors on human Tcells (33)(34)(35). Rather, IL13 is related to fibrosis of tissue in various chronic types of inflammation because IL13Rs are expressed on endothelial cells, fibroblasts, and smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms can lead to motor neuron injury, which funnel into a final pathway or noncell-autonomous toxicity and neuroinflammation leading to motor neuron death [59][60][61][62][63]. In contrast, M2 produce high levels of antiinflammatory cytokines and neurotrophic factors including IL-4, IL-10, and insulin-like growth factor (IGF)-1 in addition other neruoprotection signals such as CD200 and fractalkine [51,60,[64][65][66][67][68].…”
Section: Microgliamentioning
confidence: 99%
“…Moreover, recent studies have indicated that expression of KCCN4, the gene that encodes the KCa3.1 channel, is upregulated in IL-4-treated human macrophages. 17,24 However, the expression pattern of KCa3.1 channels and their role in modulating the balance of macrophage phenotypes are still not well defined. Using the whole-cell patch clamp recording method and Western blot assays, we demonstrated increased KCa3.1 levels in IFN-γ and LPS-treated macrophages, as well as in IL-4-treated macrophages, though the increase was significantly larger in the IFN-γ and LPS-induced M1 macrophages.…”
mentioning
confidence: 99%
“…16 However, in advanced atherosclerotic lesions, the role of KCa3.1 in the pathogenesis of plaque instability and its underlying mechanisms are unknown. A recent study reported that IL-4 stimulation increases KCa3.1 current in microglia, 17 which suggests that KCa3.1 may be involved in the polarization of macrophages and atherosclerotic plaque disruption. In this study, we pharmacologically modulated KCa3.1 activity and examined how this altered macrophage phenotype and determined its effect on plaque stability.…”
mentioning
confidence: 99%